ReDIP, the Italian network for the diagnosis of congenital platelet function disorders - Marco Cattaneo; Claudia Ghali; Mariangela Scavone (Bleeding, Thrombosis and Vascular Biology)
Congenital platelet function disorders (cPFD) are associated with an increased risk of mucocutaneous bleeding of various levels of severity; they may be classified based on abnormalities of platelet components that share common characteristics: i) platelet receptors for adhesive proteins; ii) platelet receptors for soluble agonists; iii) platelet granules; iv) signal transduction pathways; v) procoagulant phospholipids; less well characterized PFD aregrouped in a sixth category of miscellaneous abnormalities [...].